Evaluation of The Visual Landscape Quality of Parks: The Case of Serik/Antalya - Rifat Olgun (Turkish Journal of Agriculture: Food Science and Technology)
The visual perception of landscapes is expressed as seeing the qualities of the landscape. This level of perception varies depending on the socio-cultural and economic structure of the people and the environment in which they live. The fact that the environment in which people live has a variable visual structure also constantly affects their landscape perception. Parks are one of the important urban landscape areas in cities. The existing structure of the parks located in the urban landscape areas affects the visual perception value of these areas on the users. The aim of the research is to evaluate the visual landscape quality value of the parks in the city of Serik in the direction of user opinions. In this context, the photographs of the selected parks within the boundaries of the research area were taken from certain points. The questionnaire form prepared with these photographs was applied to the park users on a voluntary basis. The data obtained from the questionnaire forms were digitized and analyzed. Within the scope of the analysis, the data belonging to the socio-demographic structure of the participants and the answers they gave to the propositions about the parks were determined by descriptive analysis (frequencies and descriptives). Whether there was a statistically significant difference between the sociodemographic structure of the participants and their answers to the propositions was analyzed with parametric tests (independent sample t-test and one-way analysis of variance). At the same time, the relationship between the visual landscape quality assessment criteria of the parks was examined by Pearson Correlation Analysis. The results of the analysis show that the features of the parks due to their planning, design and maintenance affect the visual landscape quality values. In this direction, suggestions have been developed to increase the visual landscape quality value of the parks.